If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(b + -4) = 2b Reorder the terms: 3(-4 + b) = 2b (-4 * 3 + b * 3) = 2b (-12 + 3b) = 2b Solving -12 + 3b = 2b Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Add '-2b' to each side of the equation. -12 + 3b + -2b = 2b + -2b Combine like terms: 3b + -2b = 1b -12 + 1b = 2b + -2b Combine like terms: 2b + -2b = 0 -12 + 1b = 0 Add '12' to each side of the equation. -12 + 12 + 1b = 0 + 12 Combine like terms: -12 + 12 = 0 0 + 1b = 0 + 12 1b = 0 + 12 Combine like terms: 0 + 12 = 12 1b = 12 Divide each side by '1'. b = 12 Simplifying b = 12
| 3x^2-30x+75=x-5 | | 101-6x=39x+16 | | 7+c=13 | | 11(x+3)=4(3x-4) | | 4x^2-19x+20=4x+5 | | 46-2x=8 | | 6x+6=122-10x | | 11x+3=4(3x+4) | | -x^5-x^3+4x=0 | | 11x+3=4x(3x+4) | | -49-7x=9x+17 | | D-8=12 | | 20=3w-1 | | 4k-9k=10j | | 12x(3x-3)-6x(7x-9)= | | 4(2x+3)=7x+4 | | B(b-7)= | | x^2+18x+19=8x-5 | | 4(10d-4)=64 | | x^2+4x+9=6 | | 10(d-4)=60 | | 3x+2x=4x-8 | | 5(3x+3)=30 | | 2(2m-1)=18 | | 5(m-1)=30 | | 3(5a+2)=36 | | 4(2x)-(x+5)= | | 11u-88=3u | | 3(4x-1)=21 | | 0.5(9x+18)=-1.5(5x)-2(3x+4.5) | | 3x^3+26x^2+35x=0 | | 7w=5w+16 |